![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
ta có: \(x\sqrt{x}+y\sqrt{y}\ge x\sqrt{y}+y\sqrt{x}\) (1)
\(\Leftrightarrow\left(\sqrt{x}+\sqrt{y}\right)\left(x-\sqrt{xy}+y\right)\ge\sqrt{xy}\left(\sqrt{x}+\sqrt{y}\right)\)
\(\Leftrightarrow\left(\sqrt{x}+\sqrt{y}\right)\left(x-\sqrt{xy}+y-\sqrt{xy}\right)\ge0\)
\(\Leftrightarrow\left(\sqrt{x}+\sqrt{y}\right)\left(\sqrt{x}-\sqrt{y}\right)^2\ge0\) luôn đúng
=> (1) luôn đúng => đpcm
ko bít ????????????????????????????______________________________________????????????????????????????????????????
![](https://rs.olm.vn/images/avt/0.png?1311)
bài 2 : ĐKXĐ : \(x\ge0\) và \(x\ne1\)
Rút gọn :\(B=\frac{\sqrt{x}+1}{\sqrt{x}-1}-\frac{\sqrt{x}-1}{\sqrt{x}+1}-\frac{5\sqrt{x}-1}{x-1}\)
\(B=\frac{\left(\sqrt{x}+1\right)\left(\sqrt{x}+1\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}-\frac{\left(\sqrt{x}-1\right)\left(\sqrt{x}-1\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}-\frac{5\sqrt{x}-1}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}\)
\(B=\frac{x+2\sqrt{x}+1-x+2\sqrt{x}-1-5\sqrt{x}+1}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}\)
\(B=\frac{-\sqrt{x}+1}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}\)
\(B=\frac{-1}{\sqrt{x}+1}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(2,\)
\(a,\sqrt{x^2-4x+3}=3\)
\(\Rightarrow x^2-4x+3=9\)
\(\Rightarrow x^2-4x-6=0\)
\(\Rightarrow\left(x-2\right)^2=10\)
\(\Rightarrow\orbr{\begin{cases}x-2=\sqrt{10}\\x-2=-\sqrt{10}\end{cases}\Rightarrow\orbr{\begin{cases}x=2+\sqrt{10}\\x=2-\sqrt{10}\end{cases}}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\Leftrightarrow\sqrt{\left(\sqrt{x}+1\right)^2}=2\Leftrightarrow\sqrt{x}+1=2\Leftrightarrow\sqrt{x}=1\Leftrightarrow x=1\)
\(\Leftrightarrow\sqrt{\left(\sqrt{x}-2\right)^2}=3\Leftrightarrow\sqrt{x}-2=3\Leftrightarrow\sqrt{x}=5\Leftrightarrow x=25\)
\(\sqrt{x-2\sqrt{x-1}}=\sqrt{x-1-2\sqrt{x-1}+1}=\sqrt{\left(\sqrt{x-1}-1\right)^2}=\sqrt{x-1}-1=2\)
\(\Leftrightarrow x=10\)
ĐKXĐ tự tìm\(b,\sqrt{x-4\sqrt{x}+4}=3\)
\(\Leftrightarrow\sqrt{\left(\sqrt{x}-2\right)^2}=3\)
\(\Leftrightarrow\sqrt{x}-2=3\)
\(\Leftrightarrow\sqrt{x}=5\)
\(\Rightarrow x=5^2=25\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(dkxd\Leftrightarrow\hept{\begin{cases}x\ge0\\\sqrt{x}-2\ne0\end{cases}\Rightarrow\hept{\begin{cases}x\ge0\\x\ne4\end{cases}}}\)
\(A=\left(\frac{\sqrt{x}}{x-4}-\frac{2}{\sqrt{x}-2}+\frac{1}{\sqrt{x}+2}\right):\frac{1}{\sqrt{x}+2}.\)
\(=\left(\frac{\sqrt{x}}{x-4}-\frac{2\left(\sqrt{x}+2\right)}{x-4}+\frac{\sqrt{x}-2}{x-4}\right):\frac{1}{\sqrt{x}+2}\)
\(=\frac{\sqrt{x}-2\sqrt{x}-4+\sqrt{x}-2}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}.\frac{\sqrt{x}+2}{1}\)
\(=\frac{-6\left(\sqrt{x}+2\right)}{\left(\sqrt{x}+2\right)\left(\sqrt{x}-2\right)}=-\frac{6}{\sqrt{x}-2}\)
\(A=\)\(\left(\frac{\sqrt{x}}{x-4}+\frac{2}{2-\sqrt{x}}+\frac{1}{\sqrt{x}+2}\right)\)\(:\frac{1}{\sqrt{x}+2}\)
a,ĐKXĐ:\(\hept{\begin{cases}x\ge0\\2-\sqrt{x}\\x-4\ne0\end{cases}\ne0}\)\(\Rightarrow\)\(\hept{\begin{cases}x\ge0\\x\ne4\end{cases}}\)
\(A=\)\(\left(\frac{\sqrt{x}}{x-4}+\frac{2}{2-\sqrt{x}}+\frac{1}{\sqrt{x}+2}\right)\)\(:\frac{1}{\sqrt{x}+2}\)
\(A=\)\(\left(\frac{\sqrt{x}}{x-4}-\frac{2}{\sqrt{x}-2}+\frac{1}{\sqrt{x}+2}\right)\)\(.\left(\sqrt{x}+2\right)\)
\(A=\)\(\left(\frac{\sqrt{x}-2\left(\sqrt{x}+2\right)+\sqrt{x}-2}{x-4}\right)\)\(.\left(\sqrt{x}+2\right)\)
\(A=\)\(\left(\frac{\sqrt{x}-2\sqrt{x}-4+\sqrt{x}-2}{x-4}\right)\)\(.\left(\sqrt{x}+2\right)\)
\(A=\)\(\left(\frac{-6}{x-4}\right)\)\(.\left(\sqrt{x}+2\right)\)
\(A=\)\(\frac{-6}{\sqrt{x}-2}\)
b,\(x=9-4\sqrt{5}\)\(\Rightarrow\)\(A=\)\(\frac{-6}{\sqrt{9-4\sqrt{5}}-2}\)\(=\frac{-6}{\sqrt{5-2.2\sqrt{5}+4}-2}\)
\(A=\)\(\frac{-6}{\sqrt{\left(\sqrt{5}-2\right)^2}-2}\)\(=\frac{-6}{\sqrt{5}-2-2}\)\(=\frac{-6}{\sqrt{5}-4}\)
c,\(A>-1\)\(\Rightarrow\)\(\frac{-6}{\sqrt{x}-2}\)\(>-1\)\(\Rightarrow\)\(\frac{-6}{\sqrt{x}-2}+1>0\)
\(\Leftrightarrow\)\(\frac{-6+\sqrt{x}-2}{\sqrt{x}-2}>0\)
\(\Leftrightarrow\)\(\frac{\sqrt{x}-8}{\sqrt{x}-2}>0\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\sqrt{x-1}\ge0\Leftrightarrow x\ge1\)
\(\sqrt{x-1}\ne\sqrt{2}\Leftrightarrow x-1\ne2\Leftrightarrow x\ne3\)
=.= hok tốt!!
\(\frac{\left(x-3\right)\left(\sqrt{x-1}+\sqrt{2}\right)}{\left(\sqrt{x-1}-\sqrt{2}\right)\left(\sqrt{x-1}+\sqrt{2}\right)}\)
\(=\frac{\left(x-3\right)\left(\sqrt{x-1}+\sqrt{2}\right)}{x-1-2}\)
\(=\frac{\left(x-3\right)\left(\sqrt{x-1}+\sqrt{2}\right)}{x-3}=\sqrt{x-1}+\sqrt{2}\)
\(A>0\Leftrightarrow\sqrt{x}-x>0\)
\(\Leftrightarrow\sqrt{x}>x\Leftrightarrow x>x^2\)
\(\Leftrightarrow x\left(x-1\right)< 0\)
\(\Leftrightarrow0< x< 1\)
\(0;1\)